The Role of ChatGPT in Enhancing the Quality of Human Resource Team Communication: An Innovative Approach in Human Resource Management - Sutrisno, Sutrisno; Suherlan; Rijal, Syamsu (ADMAN: Journal of Contemporary Administration and Management, 2024)
Effective communication stands as one of the key pillars in human resource management (HRM). Good communication among human resource team members can enhance productivity, collaboration, and job satisfaction. This research delves deeper into how ChatGPT can be effectively implemented to improve the quality of communication within HR teams and address potential challenges that may arise in the process. The research methodology involves a qualitative literature review drawing data from Google Scholar spanning from 2006 to 2023. The study results indicate that the utilization of ChatGPT in enhancing the communication quality of HR teams has proven to bring significant benefits across various aspects of human resource management. With its ability to understand and respond to human conversation naturally, ChatGPT opens new opportunities in recruitment, training, performance management, and team collaboration.